Effects of Teriparatide on Bone Mineral Density and Prevention of Fragility Fractures in Saudi Arabian Subjects with Osteoporosis: A Two-Year Clinical Study from a Single Center - Mir Sadat-Ali; Abdallah Al-Omran; Khalid AlTabash; Dakheel A. AlDakheel; Salma Elansassy; Tarek Hegazi; Mona Al Muhaish (International Journal of Clinical Practice)
Background and Objective. This prospective study was conducted to evaluate changes in BMD and prevention of fragility fractures in osteoporosis patients after 24 months use of teriparatide. Design. A prospective study was conducted. Setting. This study took place at King Fahd Hospital of the University, Imam AbdulRahman Bin Faisal University, Dammam, Saudi Arabia. Primary and Secondary Outcomes. The study aimed to evaluate changes in BMD and prevention of fragility fractures. Materials and Methods. We followed up 439 patients who were prescribed teriparatide at the King Fahd Hospital of the University, AlKhobar, and 415 (94.5%) patients completed a 24-month teriparatide course. The data gathered before starting medication were age, sex, previous therapy, history of fractures, and other diseases like diabetes mellitus, hypertension, and cardiac disease. At the time of the final assessment after 24 months, a history of fractures if any during the treatment was collected and a DXA scan was done. Results. A total of 415 patients were followed up for 2 years. Three hundred and sixty-five patients (87.9%) were females, and the rest were males. The average age was 68.21 ± 17.6 years. Two hundred and forty-eight patients (59.8%) were treatment naïve, and 167 (40.2%) were on treatment for osteoporosis. Twenty patients (4.8%) sustained fracture on treatment. The pretreatment DXA showed that the mean hip T-score was −3.1 ± 0.79, and after completion of the treatment, it was −1.5 ± 0.62 P<0.001, while the T-score of the lumbar spine was 4.4 ± 0.86 versus −3.2 ± 0.87 P<0.001. Seventeen (4.09%) had fractures while on teriparatide treatment. The mean significant gain (MSG) for BMD for the hip was 0.095 g/cm2, and for the lumbar spine, it was was 0.109 g/cm2 with P<0.001 at 95% CI. Conclusions. Our study shows that 94.5% completed the treatment duration, and there was an increase in the BMD. The decrease in T-scores of the lumbar spine and hip was significant so was the reduction in the number of fractures.